Elevated salinity decreases soil ecosystem multifunctionality by shifting the bacterial community from K‐ to r‐selected living strategy. (21st November 2022) - Cheng, Yarui; Wan, Wenjie
Abstract: Deciphering ecosystem multifunctionality (EMF) driven by abiotic and biotic factors is crucial for evaluating soil nutrient cycling and retention. Yet, there is little information on whether microbial r / K ‐selection can play the same role as community diversity to reflect EMF. Using Illumina MiSeq sequencing, phospholipid fatty acid (PLFA) technique, and multiple statistical analyses, we estimated linkages among salinity, soil EMF, community diversities, microbial r / K ‐selection, and bacterial ecological assembly processes and phylogenetic signals in salinized agricultural soils (0.09–19.91 dS m −1 ). Salinity significantly negatively correlated with soil EMF, bacterial taxonomic and phylogenetic α‐diversities, and bacterial K ‐selection represented by the Acidobacteria / Proteobacteria (Aci:Pro) ratio (0–0.50). There was a significantly positive correlation between bacterial K ‐selection and soil EMF (Pearson's r = 0.545, p < 0.001). Deterministic processes (60.0–85.5%) dominated bacterial community assemblies along salinity gradients (i.e., 0–1, 1–2, 2–4, 4–8, 8–16, and >16 dS m −1 ), and salinity displayed a critical role in balancing stochastic and deterministic processes. To our knowledge, this study is the first to report elevated salinity decreased soil EMF and a bacterial shift from K ‐ to r ‐selection. Environmental constraint and phylogenetic conservatism showed strongly negative influences on bacterial K ‐selection. These findings enrich the knowledge of bacterial diversity maintenance in salinized agricultural soils and reveal close linkage between bacterial K ‐selection and soil EMF. Therefore, the bacterial K ‐selection index of Aci:Pro could serve as a bioindicator for soil EMF.